“Secret Language” in Oral and Graphic Form: Religious-Magic Discourse in Aztec Speeches and Manuscripts - Katarzyna Mikulska, Dąbrowska (Center for Studies in Oral Tradition, 2018)
The purpose of this paper is to analyze a particular linguistic register of the Nahua (Aztec) people that has been classified as “magical-religious” because it was used for communication with the sacred realm. A hypothesis is developed that in the Mesoamerican pictographic calendar-religious manuscripts, which treat matters strictly linked to the supernatural world, a similar register should be evident. Far from considering the information presented in these resources as resulting from the direct transcription of oral language, the idea is that the graphic form represents elements emblematic of orality, although adapted to this particular context and mode for expression.